Between the gothic and the pedagogical: The crisis of cholo masculinity in Fabla salvaje - Muñoz-Díaz, Javier (2021)
This article proposes that Fabla salvaje shows the crisis of the subaltern masculinity of the cholo, embodied in the tragic trajectory of the character Balta Espinar. The crisis of the cholo Balta originates in his deficient incorporation into a new hegemonic sex/gender system and a new masculinity of a literate and urban order (represented in his friends and the narrator). On the other hand, this new sex/gender system destabilizes the traditional divisions in the Serrano world-village, which explains the gender violence that Balta exercises against his wife, the also chola Adelaida. Finally, Fabla salvaje is interpreted at the intersection of two tendencies in Vallejo's writing: the gothic tendency (which nourishes the rhetorical arsenal) and the pedagogical tendency (which explains the function of the narrator). In that sense, Balta's crisis is not ethnic/racial, but pedagogical.